PENGUATAN PETERNAK KAMBING MELALUI PROGRAM ZAKAT COMMUNITY DEVELOPMENT DI KABUPATEN TANAH DATAR - Riza Andesca Putra; Fuad Madarisa; Roni Pazla (LPPM Universitas Andalas, 2021)
The current COVID-19 pandemic has shaken many things. This condition makes the goat breeders of the ZCD (Zakat Community Development) program in Tanah Datar Regency demotivated because many activities and businesses are hampered. This year will plan to build a feed factory due to the assistance of the central ZCD and the establishment of business institutions. Until now, the plan is running in place because all activities that cause crowds have stopped. Sales of products, in the form of goats, also experienced significant disruptions. Moving on from these conditions, we held service activities with training and mentoring methods. The objectives of this activity are 1. They are renewing the enthusiasm and motivation of farmers in running a business, 2, providing knowledge and knowledge on how and stages of establishing a mini-feed factory, 3—providing knowledge and knowledge about the establishment of livestock business institutions. From the results of the activities obtained: (1), The COVID-19 pandemic has indeed disrupted the implementation of the ZCD program in Tanah Datar Regency (including the motivation of farmers), especially activities related to human interaction, but is currently recovering (2) Plans for establishing a mini-feed factory for implementation in 2021. However, breeders and managers better understand the stages to be carried out (3) ZCD managers already understand the plan to establish a livestock business institution to capture a reasonably large goat market opportunity from the internal of National Zakat Agency. The results of this activity suggest: (1) ZCD program activities should be re-run by applying the existing health protocols, (2) Establishment of ZCD member business institutions must be carried out immediately and recommended in the form of cooperatives.